2015
DOI: 10.1021/acs.jcim.5b00265
|View full text |Cite
|
Sign up to set email alerts
|

Binding Kinetics versus Affinities in BRD4 Inhibition

Abstract: Bromodomains (BRDs) are protein modules that selectively recognize histones as a "reader" by binding to an acetylated lysine substrate. The human BRD4 has emerged as a promising drug target for a number of disease pathways, and several potent BRD inhibitors have been discovered experimentally recently. However, the detailed inhibition mechanism especially for the inhibitor binding kinetics is not clear. Herein, by employing classical molecular dynamics (MD) and state-of-the-art density functional QM/MM MD simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…Comparing RMSFs between apo and holo BDs in both systems, we found that BC loop almost kept unchangeable during the simulation, whereas the flexibility of ZA loop notably decreased upon binding to RVX-208. It is in accordance with the previously reported results of other inhibitor-BD systems 37 , 38 . The higher flexibility decreasing of ZA loop of BD2 relative to BD1 indicated that BD2 pocket might undergo conformational rearrangement due to the binding of RVX-208.…”
Section: Resultssupporting
confidence: 94%
“…Comparing RMSFs between apo and holo BDs in both systems, we found that BC loop almost kept unchangeable during the simulation, whereas the flexibility of ZA loop notably decreased upon binding to RVX-208. It is in accordance with the previously reported results of other inhibitor-BD systems 37 , 38 . The higher flexibility decreasing of ZA loop of BD2 relative to BD1 indicated that BD2 pocket might undergo conformational rearrangement due to the binding of RVX-208.…”
Section: Resultssupporting
confidence: 94%
“…27 This protein is particularly suitable for this type of calculation, since the ligands bind near its surface and with clear access to the solvent, avoiding steric clashes during the pulling process. It is worth noting that the first BRD4 bromodomain has already been the target of numerous computational studies on ligand binding, using a range of methods such as fragment-based docking, 33 the MM-PBSA/GBSA method combined with steered molecular dynamics (SMD), 34 and free energy techniques, such as umbrella sampling, 35 ABF, 21 and alchemical methods. 11 In this last study, Aldeghi et al computed the binding free energies of several molecules to the BRD4 bromodomain, starting both from the crystal structure complexes and the binding poses obtained after performing protein–ligand rigid docking, and obtained encouraging agreement with experiment.…”
Section: Introductionmentioning
confidence: 99%
“…A similar procedure was also performed for a series of additional bromodomains. 18 In another computational study, Kuang et al 35 noted a conformational change in the protein’s ZA-loop, which occurs in the absence of bound ligands and produces an apo conformation slightly different from the crystal structure. In the present study, as part of the binding free energy calculations, we also investigate conformational changes in the apo protein, using the APR method to obtain the free energies associated with this process.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Functionally, it acts as a chromatin reader that specifically recognizes the acetylated lysine in histone tails and facilitates the localization of chromatin regulatory cofactors, thereby regulating transcription initiation and elongation. 12 , 13 BRD4 also serves as a mitotic bookmark and plays a key role in cell cycle progression. 14 Ectopic expression of BRD4 in cultured cells results in G1/S arrest, while inhibition of BRD4 function by injection of anti-BRD4 antibodies arrests cells in G2/M phase.…”
mentioning
confidence: 99%